2008
DOI: 10.1111/j.1442-200x.2008.02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple drug‐resistant gene 1 in children with steroid‐sensitive nephrotic syndrome

Abstract: PGP may play a role in the tapering of corticosteroids after CR in SSNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…Wasilewska et al [38] measured P-gp expression on CD3-positive lymphocytes and found that CD3/P-gp expression was significantly higher in patients with NS than in the controls and that the difference was higher in steroid-dependent and frequent relapsing groups than in the non-frequent relapsing group. Funaki et al [36] reported that the MDR1 mRNA expression level in nucleated cells of peripheral blood was variable in patients with idiopathic NS prior to remission, but apparently decreased after complete remission. In another study [37], MDR1 activity and mRNA expression in peripheral lymphocytes were higher in patients with steroid-, cyclophosphamide-, or cyclosporine-resistant NS than in patients who were sensitive to those drugs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wasilewska et al [38] measured P-gp expression on CD3-positive lymphocytes and found that CD3/P-gp expression was significantly higher in patients with NS than in the controls and that the difference was higher in steroid-dependent and frequent relapsing groups than in the non-frequent relapsing group. Funaki et al [36] reported that the MDR1 mRNA expression level in nucleated cells of peripheral blood was variable in patients with idiopathic NS prior to remission, but apparently decreased after complete remission. In another study [37], MDR1 activity and mRNA expression in peripheral lymphocytes were higher in patients with steroid-, cyclophosphamide-, or cyclosporine-resistant NS than in patients who were sensitive to those drugs.…”
Section: Discussionmentioning
confidence: 98%
“…Various types of structurally unrelated drugs, including steroids, are known to be substrates for P-gp [34,35]. Several studies have been conducted to evaluate the association of P-gp expression with the responsiveness to steroids in patients with idiopathic NS [36][37][38]. Wasilewska et al [38] measured P-gp expression on CD3-positive lymphocytes and found that CD3/P-gp expression was significantly higher in patients with NS than in the controls and that the difference was higher in steroid-dependent and frequent relapsing groups than in the non-frequent relapsing group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of P-gp is associated with poor response to steroid or steroid dependence in INS [26]. Funaki et al reported decrease in the MDR1 gene expression after complete remission and advocated that P-gp may play a role in the tapering of corticosteroids after remission in steroid sensitive Nephrotic Syndrome [27]. The poor treatment response due to increased P-gp expression has also been observed in other non-nephrological conditions like patients with malignancies [28], systemic lupus erythematosus [29], inflammatory bowel disease [30], rheumatoid arthritis, and other autoimmune diseases [31].…”
Section: Discussionmentioning
confidence: 96%
“…The transcription of MDR1 is directly regulated by the human Y box-binding protein-1 and alterations in expression are seen in response to a range of stimuli including steroid exposure. 18 Narang et al 6 exposed rat brain microvascular endothelial cells to dexamethasone and found both a dose-dependent and reversible increase in MDR1 transcription as early as 6 hours. These findings have been replicated in the LS180 small intestinal cell line; 2 however, conflicting results have been reported in other gut epithelial cell cultures as well as in the peripheral blood lymphocytes of asthmatic patients treated with inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 98%